Comparison of the Development and Prognosis in Patients of Hypertriglyceridemic Pancreatitis with and without Diabetes - Wenjian Liao; Xiuxiu Niu; Wei Zhang; Xiaobing Liu (Gastroenterology Research and Practice)
Aim. To investigate the clinical features and prognosis in patients of hyperlipidemic acute pancreatitis with or without diabetes. Methods. 157 patients with hypertriglyceridemic pancreatitis (HTGP) were included in this study. Patients with a previous history of diabetes were identified in the group of HTGP with diabetes (HTGPD), while patients without a history of diabetes were identified in the group of HTGP. The clinical characteristics and prognosis data of these patients in the two groups were analyzed. Results. Multivariate Cox regression analysis showed that age, body mass index, glycated serum protein (GSP), and Acute Physiology and Chronic Health Evaluation (APACHE) II score were significantly associated with mortality in patients with HTGP. The mortality was significantly higher in the HTGPD group than in the HTGP group (p<0.001). Compared to patients of HTGP, those of HTGPD had older age of onset, higher blood glucose levels, and higher GSP levels on admission. Electrocardiograms showed that patients of HTGPD had a significantly higher risk of heart ischemia than those of HTGP (p<0.05). Patients of HTGPD had higher APACHE II scores than those of HTGP (p<0.001). Single-factor analysis showed that higher triglyceride levels, GSP, LDL, and previous history of diabetes were associated with HTGP recurrence. Conclusions. Clinicians should be alert to patients of HTGP with diabetes. Diabetes is an important risk factor for HTGP and hyperglycemia may affect the development and prognosis of HTGP.